The Effect of Mathematics Anxiety and Intelligence on Students’ Logical Thinking Ability - Mhmd Habibi; Novia Wahyuni; Nur Rusliah; Muhammad Ilham; Intan Fitri (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2021)
This study aims to determine the effect of mathematics anxiety and intelligence on students' logical thinking skills. Which involved 96 respondents at high school. The research instruments used in this study were mathematics anxiety questionnaires, intelligence test questions, and logical thinking ability test questions. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that there is an effect of mathematics anxiety and intelligence on students' logical thinking abilities.